Emerging trends in language learning strategy use among net-generation ESL tertiary learners - Shakarami, Alireza (2011)
Since 1975, various theories and models have classified learners according to type, style, and language learning strategy use. All the existing theories however, were developed in the years before the pervasion of computer technology, Internet use and the globalisation of knowledge. The new-millennial learners of today have grown up in the era of information explosion, Internet, and online communication opportunities that immerse them in ICT culture. These Net-Generation learners learn and communicate with minimal time and space limitations, and utilise new knowledge and skills to participate in new forms of learning and social communities. In the light of these changing dynamics, the present study explored whether Malaysian Net-Geners use language learning strategies as earlier generations of learners did, and whether there are emerging trends in the strategies use not addressed in extant theories. The researcher first obtained quantitative data from 107 ESL tertiary learners about their strategy use based on Oxford‟s (1989) widely used Strategy Inventory for Language Learning (SILL), currently considered the most comprehensive inventory. Data on strategy use was then procured using qualitative methods: semi-structured interviews, journal entries, open-ended questionnaires, and texts of the respondents‟ online interaction in a language task. This latter set of data was analysed (i) to compare the qualitative data with the SILL data, and (ii) to identify possible emergent strategies or trends in strategy use among Net-Geners. The findings indicate that Net-Geners still made use of language learning strategies identified in extant inventories, but there are perceptible changes in the form of social, memory, and affective strategy use. Minor changes were observed in the use of metacognitive, cognitive, and compensation strategies. While the SILL data showed a lower level of importance put on social and affective strategies, the qualitative data indicated that the respondents were heavily dependent on those strategies. Memory strategy use was also ranked low on the SILL, but the study found that the respondents did substantially utilise „memory‟ in electronic form. Slightly different representations of metacognitive, cognitive, and compensation strategies were found to be used by the respondents. Emergent trends in strategy use that are not addressed in the SILL include:multi-tasking, visual dependency, language customisation, language democratisation, distributed cognition or cognition sharing, growing tendency toward more paper-less learning, and change in the notions of privacy and authorship. These findings point to a need to rethink what we currently understand about language learning strategies and to take a fresh look at what „works‟ for Net-Generation learners. The existence of some incongruence between SILL data and the qualitative data, as well as the emergence of new trends not apparently captured in the SILL or other existing inventories, suggest a need for further similar research on other groups of Net-Geners, and a revision of currently available language learning inventories in order to incorporate and better describe the emerging skills and strategies of Net-Geners. Based on the findings of the study a model of language learning in the ICT-mediated context of learning is proposed and suggestions are made regarding the modification of existing inventory items as well as the inclusion of new ones that would make an inventory more compatible with language learning strategy use in the digital era. The proposed model could be used as a basis for the development of a new and more relevant language learning inventory that addresses the language learning needs of Net-Geners in the networked world.